Perlindungan Hukum Terhadap Perempuan Dan Anak Di Tinjau Dari Hukum Humaniter Internasional - Latubual, Godlief Niclas Wenetama; Wattimena, Josina Augustina Yvonne; Hanafi, Irma Halimah (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: As a result of the prolonged conflict between Israel and Palestine, many children and women who have been affected by this conflict have suffered and even died as a result of this war. This unresolved conflict has resulted in a large number of victims from civil society from year to year and is increasing, especially children. Children who should have the right to grow and develop naturally when the war rages all their rights become victims of war, children's rights to grow up are violated without any mercy towards them, whatever the reason for the conflict, this act is a crime against humanity. and violations of children's rights.Purposes of the Research: This writing aims to analyze and find out the legal arrangements for women and children in armed conflicts in terms of international humanitarian law, to analyze and find out the forms of legal protection for women and children in armed conflicts, and as one of the requirements in completing studies at the University Law Faculty Pattimura.Methods of the Research: Normative research method with the type of research is qualitative analysis. The problem approach used is the statute approach, the conceptual approach and the case approach. The sources of legal materials used are Primary legal materials, Secondary legal materials, and Tertiary legal materials and are used as a technique for collecting legal materials, then processing and analyzing legal materials through methods of interpretation, harmonization, systematic and legal discovery.Results of the Research: The results of the study indicate that the legal arrangements for women and children in armed conflict are reviewed from international humanitarian law, namely Additional Protocol II of 1977 concerning the Protection of Victims of Non-International Armed Conflicts, which in Article 4 stipulates that everyone is not directly involved or is no longer involved. in a non-international armed conflict must be treated humanely and no distinction should be made that is detrimental to them. Provisions of the International Covenant on Civil and Political Rights (ICCPR) Article 4 which requires that even in a precarious public situation, fundamental non-derogable rights must still be respected.